Eksistensi Bank Tanah Terkait Pengadaan Tanah Berdasarkan Undang-Undang Cipta Kerja - Nila Erdiana; Budi Santoso; Mujiono Hafidh Prasetyo (Magister Kenotariatan Universitas Diponegoro, 2021)
Regarding land sector, Job Creation Law has included regulation regarding existence of Land Banking in Indonesia. The purpose of writing this article is to examine and analyze how existence of Land Banking is related to land acquisition based on the Job Creation Law and its derivative regulations. The research method in this article is juridical normative. The existence of Land Banking related to land acquisition based on Job Creation Law includes: First, legitimacy of establishing Land Banking. Article 125 paragraph (1), (2) and (3) of the Job Creation Law states that the Central Government establishes Land Banking, which is a special agency that manages land and its assets are separated state assets. Second, structure of Land Banking organs consists of: Committee; Supervisory Board; and Implementing Agency. Third, Land Banking functions to carry out planning, acquisition, procurement, management, utilization and distribution of land. Fourth, the character of duties and authorities of Land Banking is transparent, accountable, and non-profit. Fifth, sources Land Banking assets can come from: State Budget; Own income; State equity participation; and other legitimate sources. Sixth, land managed by Land Banking is granted management rights.Keywords: Land Banking; Job Creation Law; Land AcquisitionAbstrakTerkait bidang pertanahan, UU Cipta Kerja telah menyisipkan pengaturan mengenai eksistensi Bank Tanah di Indonesia. Tujuan penulisan artikel ini adalah mengkaji dan menganalisis bagaimana eksistensi Bank Tanah terkait pengadaan tanah berdasarkan UU Cipta Kerja serta peraturan turunannya. Metode penelitian dalam artikel ini adalah yuridis normatif. Eksistensi Bank Tanah terkait pengadaan tanah berdasarkan UU Cipta Kerja meliputi: Pertama, legitimasi pembentukan Bank Tanah. Pasal 125 ayat (1), (2) dan (3) UU Cipta Kerja menyatakan bahwa Pemerintah Pusat membentuk Bank Tanah, yang merupakan badan khusus yang mengelola tanah dan kekayaannya merupakan kekayaan negara yang dipisahkan. Kedua, struktur organ Bank Tanah terdiri atas Komite, Dewan Pengawas, serta Badan Pelaksana. Ketiga, Bank Tanah berfungsi melaksanakan perencanaan, perolehan, pengadaan, pengelolaan, pemanfaatan, dan pendistribusian tanah. Keempat, sifat tugas dan wewenang dari Bank Tanah adalah transparan, akuntabel, dan non profit. Kelima, sumber kekayaan Bank Tanah dapat bersumber dari: APBN; Pendapatan sendiri; Penyertaan modal negara; dan sumber lain yang memiliki kebasahan. Keenam, tanah yang dikelola Bank Tanah diberikan hak pengelolaan.Kata kunci: Bank Tanah; UU Cipta Kerja; Pengadaan Tanah